Making learning fun in the classroom: a serious undertaking - Adão, Teresa (2016)
The importance of humour has been increasing the interest in its potential applications in a variety of professional domains. This is the case of education which was traditionally seen as a serious undertaking where there was no place for humour. However it is now understood that it is possible and very advantageous to make learning fun. In the classroom, teachers should assume the role of learning mediators, so it seems pertinent to assess teachers’ ability to process humour information through humorous texts. Accepting the general research lines of Fauconnier and more recently of Ritchie, every humorous text follows a mechanism in which there is an initial part, called the set-up, appearing to have one interpretation, and a final part, the punchline, which provokes a mental shifting and forces the reader or the hearer to perceive another point of view. This change of interpretation does not mean the former was incorrect, but it is needed because it is responsible for the incongruity resolution without which the humour language comprehension does not happen and consequently there is no humour appreciation.w So the incongruity-resolution model of humour was tested by a series of humorous sketches each one followed by four possible endings among which the true funny punchline could be found. It has been asked the participants to complete the sketches by selecting one of the four options which they thought it was the funny ending. The results of this research showed evidence that teachers understand the language of humour.